Anniversary meeting: 30 November 1983 - -, - (Proceedings of the Society of Antiquaries of Scotland, 1984)
At the Anniversary meeting the Annual Report was delivered covering topics such as Membership, Meetings, Research and publications. The Treasurer then presented the report on the Society’s accounts. The Council for the following session was then elected and a list of Fellows who died during 1982-1983 was read.